Consumer Assessment of Healthcare Providers and Systems (CAHPS®) survey of experiences with ambulatory healthcare for Asians and non-Hispanic Whites in the United States - Mohir Ahmedov; Nadereh Pourat; Honghu Liu; Ron D. Hays (SpringerOpen, 2021)
Abstract Background Differences in experiences of care reported by Asian Americans (Asians) compared to non-Hispanic Whites (Whites) may be due to lack of measurement invariance. Methods We evaluated the three-factor structure and the equivalence of responses to the Consumer Assessment of Healthcare Providers and Systems (CAHPS®) Clinical and Group (CG-CAHPS) Adult Visit Survey 1.0 and compared care experiences of Asians and Whites. Thirteen questions were used to elicit reports about specific aspects of care and two questions assessed overall care perceptions. This analysis of the CAHPS database included 769 providers and 266,327 respondents. Most surveys (98%) were administered by mail and the rest (2%) by phone. Only 0.5% of the surveys were administered in Spanish. The sample was 64% female, 89% White and 2% Asian, 39% 65 years or older, and 32% were high school graduates or less. Results A three-factor model was supported by categorical confirmatory factor analysis using weighted least squares with mean and variance adjustment: confirmatory fit index (CFI) = 0.99 and root mean squared error of approximation (RMSEA) = 0.03). A multi-group configural invariance model also fit the data well: (CFI = 0.993, RMSEA = 0.031). Regression models indicated that Asians reported worse access, lower scores on office staff courtesy and helpfulness and rating their doctors and were less likely to recommend their doctors to family/friends than did Whites. Conclusions Use of the CG-CAHPS Adult Visit Survey 1.0 to assess perceptions of care by Asians and Whites is supported. Quality improvement efforts are needed to address worse experiences of care among Asians in the United States.